1993
DOI: 10.1212/wnl.43.6.1088
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe hypometabolism on PET

Abstract: To investigate the relationship of temporal lobe hypometabolism demonstrated on PET to surgical outcome and underlying pathology, we reviewed 30 consecutive epilepsy patients who underwent interictal PET studies with 18F fluorodeoxyglucose before temporal lobectomy. Two interpreters blindly reviewed the PET studies and graded them for degree, extent, and location of temporal lobe hypometabolism. Pathologic analysis of en bloc resected tissue showed mesial temporal sclerosis (n = 22), astrocytoma (n = 2), and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 0 publications
6
58
0
Order By: Relevance
“…In our population, lateralized hippocampal atrophy was strongly correlated with seizure-free outcome (class I), and relative focal TL hypometabolism with FDG-PET correlated with a good outcome (classes I and II). These results for MRI and FDG-PET are consistent with previous studies [5,[36][37][38]. T2 relaxometry also correlated with good outcome, but it appears to only reflect detection of the same patients as HV.…”
Section: Correlation With Outcomesupporting
confidence: 90%
“…In our population, lateralized hippocampal atrophy was strongly correlated with seizure-free outcome (class I), and relative focal TL hypometabolism with FDG-PET correlated with a good outcome (classes I and II). These results for MRI and FDG-PET are consistent with previous studies [5,[36][37][38]. T2 relaxometry also correlated with good outcome, but it appears to only reflect detection of the same patients as HV.…”
Section: Correlation With Outcomesupporting
confidence: 90%
“…As early as 1987, Engel (1) noted that those patients studied before the introduction of the PET scan in the presurgical protocol at UCLA had a less favorable outcome. Others also reported that FDG-PET temporal hypometabolism (23,24), as well as MRI evidence of HS, correlates with a better outcome (25).…”
Section: Late Recurrencesmentioning
confidence: 97%
“…Greater severity of the preoperative abnormality visualized by PET is associated with better postsurgical seizure control (58,59). …”
Section: Unilateral Mtsmentioning
confidence: 99%